Klappertart berbasis buah siwalan dan tepung ganyong sebagai variasi makanan modern: Potensi dan tantangan - Elma Sulistiya; Novi Indah Permata Sari; Heni Adhianata; Filias Kusuma (ARGIPA (Arsip Gizi dan Pangan), 2026)
Klappertart is a traditional Indonesian dessert from Manado, originally made from coconut, milk, eggs, and wheat flour. Innovation using local ingredients is needed to enhance nutritional value and support national food diversification. This review aims to examine the potential and challenges of developing klappertart based on siwalan fruit (Borassus flabellifer) and canna flour (Canna edulis) as a functional, and sustainable food variation. Siwalan fruit, a local palm commodity, contains natural sugars, dietary fiber, and bioactive compounds such as phenolics and flavonoids that act as natural antioxidants. Canna flour is a non-gluten starch source rich in complex carbohydrates and resistant starch, contributing to digestive health. The combination of these ingredients can produce klappertart with a soft texture, unique flavor, and improved functional properties. However, several challenges remain, including raw material standardization, product stability, and shelf-life optimization. This review highlights the need for applied research, formulation innovation, and policy support to strengthen the development of siwalan–canna klappertart as a modern food product based on Indonesia’s local resources.